2020
DOI: 10.1177/2047173420948411
|View full text |Cite
|
Sign up to set email alerts
|

Financial citizenship as a broader democratic context of financial literacy

Abstract: Financial citizenship is crucial in our modern world. Financial citizenship is underpinned by the education of future generations so that they can understand both their local and global economies to make the best financial decisions concerning their lives. This paper discusses financial literacy, how it relates to individual citizens, and how it correlates with social, political and business spheres. According to current financial capability models, every individual’s financial well-being can be boosted by dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Instead, the future of financial literacy teaching and learning will depend upon its presumptive societal significance. Here, citizenship education, including criticism and discussion (Khalil, 2021;Lefrançois et al, 2017), cannot only educate independent and self-sufficient individual, but also help students to grasp financial concepts and further understand financial and societal prerequisites important for their future (cf. Biesta, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the future of financial literacy teaching and learning will depend upon its presumptive societal significance. Here, citizenship education, including criticism and discussion (Khalil, 2021;Lefrançois et al, 2017), cannot only educate independent and self-sufficient individual, but also help students to grasp financial concepts and further understand financial and societal prerequisites important for their future (cf. Biesta, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this field of teaching, the democratic aspects of being financially educated and able are put forward (Amagir et al, 2018) and neo-classical aims of traditional financial literacy education should be disclosed and discussed (Sonu and Marri, 2018). Several studies argue for the use of Westheimer and Kahne's (2004) conceptions of citizenship when teaching financial literacy (Björklund and Sandahl, 2020;Khalil, 2021;Lefrançois et al, 2017;Lucey and Bates, 2012) which emphasise that financial education should support individuals' ability to take active part in current society as well as the ability to take leadership in future financial and societal change.…”
Section: Financial Literacy Education: Origin and Implementationmentioning
confidence: 99%
“…In 2009, Leyshon defined "financial citizenship" as a "concept that recognizes the significance of the financial system to everyday life and confers a right and ability on individuals and households to participate fully in the economy and to accumulate wealth" [48]. As such the concept of financial citizenship intends to contribute to a "critical reevaluation of the concept of financial inclusion" [48], which has been criticised for yielding only marketbased interventions that engage individuals purely as consumers rather than citizens [48,54]; for focusing on access over usage [59]; and for introducing new problems, such as indebtedness [4].…”
Section: Financial Citizenshipmentioning
confidence: 99%
“…Westheimer and Kahne (2004) concluded that personally responsible citizenship, participatory citizenship, and justice-oriented citizenship are the three conceptions of citizenship based on practices for democratic citizenship and educational theories. Here, Khalil (2021) distinguished these three conceptions of citizenship by offering core assumptions. Personally responsible citizens should be honest, law-abiding, and have good character in order to improve society and solve social problems.…”
Section: Introductionmentioning
confidence: 99%
“…Participatory citizens should take leadership roles and be active in order to improve society and solve social problems. Justice-oriented citizens should be critical about political, social, and economic structures in order to improve society and solve social problems (Khalil, 2021). Recent studies, on the other hand, have suggested pluralistic or multicultural citizenship, which are interwoven with critical democratic citizenship (Mathews and Dilworth, 2008; Knowles, 2018; Rodriguez, 2018; Shanks, 2019; Falkner and Payne, 2021).…”
Section: Introductionmentioning
confidence: 99%